Autodemarcação e territorialidade do povo Tuxá - Moraes, Vanessa Coelho (2024)
This research was developed based on ethnography with the Tuxá people. These people descend from a group of people who inhabited the sub-middle region of the São Francisco River and as a result of colonial violence, the area of occupation of the old city of Rodelas was reduced, which was flooded by the Itaparica dam. As a consequence, part of the ethnic group went to other cities, this study focused on those who continued to reside in the new city of Rodelas and next to it in Aldeia Mãe. This entire process of violence and expropriation will be analyzed from the perspective of theories of territoriality and deterritorialization . The research analysis will focus on an understanding of Tuxá identity and territoriality in its recent re-territorialization process in the territory of Dzorobabé, which corresponds to the place that was close to the ancient island Surubabel, called Dzorobabé in the Dzubukua-Tuxá language. In 2017, they began to self-demarcate this place, organizing themselves into clans and building sheds, kitchens and bathrooms, so that a systematic occupation was possible, which aims to compose a strategy that pressures the state to take the necessary measures for demarcation. This dissertation aims to describe and critically analyze this process, highlighting the legitimacy of the claim to the Tuxá territory and its strategies to consolidate the guarantee of its rights.